Breaking Bones to Obtain Marrow: A Comparative Study between Percussion by Batting Bone on an Anvil and Hammerstone Percussion. (24th February 2014) - Blasco, R.; Domínguez‐Rodrigo, M.; Arilla, M.; Camarós, E.; Rosell, J.
<x xml:space="preserve">Abstract</x> The fat‐ and nutrient‐rich marrow of animal bones can be extracted using different techniques. Passive hammerstone percussion has been the primary focus of experimental bone breaking and the main analogy to understand archaeological bone breakage. Here, the term 'passive' is applied because the bone to be broken passively receives the impact from a hammerstone. In addition to this technique, there is another bone‐breaking method that also requires direct percussion, but in an active way. This method is percussion by 'batting', in which the bone is actively hit against an anvil until the bone breaks. This technique has rarely been considered at an experimental level and, therefore, has been omitted in the majority of the archaeological interpretations of faunal assemblages with pre‐use of fire technologies. In this study, we attempt to analytically characterize this type of bone‐breaking technique through a systematic comparison with hammerstone percussion. The applied statistical tests will allow us to distinguish some diagnostic modifications, such as the outlines of the fracture planes and the type of notches or their location with respect to the longitudinal axis of the bone. These features and their proportions allow the consideration of the use of this technique in Pleistocene anthropogenic faunal assemblages.